Hong Kong Chinese school children with elevated urine melamine levels: A prospective follow up study - Chu Winnie CW; Liu Eric KH; Wong Chun; Chan Michael HM; Ho Chung; Choi Kai-Chow; Kong Alice PS; Chow Viola CY; Lau Joseph TF; Chan Juliana CN (BMC, 2011)
Abstract Background In 2008, the outbreak of kidney stones in children fed by melamine-tainted milk products in Mainland China has caused major public concern of food safety. We identified Hong Kong school children with elevated urine melamine level from a community-based school survey in 2007-08 and reviewed their clinical status in 2009. Methods In 2007-08, 2119 school children participated in a primary and secondary school survey in Hong Kong using a cluster sampling method. Urine aliquots from 502 subjects were assayed for melamine level. High urine melamine level was defined as urine melamine/creatinine ratio >7.1 μg/mmol. Subjects with high urine melamine level were invited for clinical evaluation in 2009 including urinalysis and ultrasound imaging of the urinary system. Results The age range of this subcohort was 6 - 20 years with 67% girls (335 female and 167 male subjects). The spot urine melamine/creatinine ratio of the 502 urine aliquots ranged from undetectable to 1467 μg/mmol (median 0.8 μg/mmol). Of these, 213 subjects had undetectable level (42%). We invited 47 (9%) subjects with high urine melamine level for re-evaluation and one subject declined. The median duration of follow-up was 23.5 months (interquartile range: 19.8 - 30.6 months). None of the 46 subjects (28% boys, mean age 13.9 ± 2.9 years) had any abnormality detected on ultrasound study of the urinary system. All subjects had stable renal function with a median urine albumin-creatinine ratio of 0.70 mg/mmol (interquartile range: 0.00 - 2.55 mg/mmol). Conclusions Hong Kong Chinese school children with high urine melamine levels appeared to have benign clinical course in the short term although a long term follow-up study is advisable in those with persistently high urine melamine level.